2018
DOI: 10.1111/neup.12472
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomes, autophagosomes and Alzheimer pathology in dementia with Lewy body disease

Abstract: A failure of protein degradation may underpin Lewy body disease (LBD) where α-synuclein is assimilated into the pathognomic Lewy bodies and Lewy neurites. We investigated histological alterations in lysosomes and autophagosomes in the substantia nigra (SN) and cingulate gyrus (CG) in 34 patients with LBD employing antibodies against phosphorylated α-synuclein and lysosomal (lysosomal associated membrane proteins 1 and 2 (LAMP-1 and LAMP-2), cathepsin D (CTSD)) and autophagosomal (microtubule-associated protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 46 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…Consistent with previous results, the brain displayed a substantial increase in magnitude changes as compared to the retina (Koronyo et al, 2017; Koronyo‐Hamaoui et al, 2011). Finally, the lysosomal‐associated membrane protein 1/2 (LAMP1/2) molecules have also been implicated in the degradation of Aβ fibrils (Barrachina et al, 2006; Gurney et al, 2018) and were found to be up‐regulated in brain and retinal tissues from old ADtg mice. In response to GA immunomodulation, we revealed a preferential down‐regulation of LAMP1 in the brain and LAMP2 in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with previous results, the brain displayed a substantial increase in magnitude changes as compared to the retina (Koronyo et al, 2017; Koronyo‐Hamaoui et al, 2011). Finally, the lysosomal‐associated membrane protein 1/2 (LAMP1/2) molecules have also been implicated in the degradation of Aβ fibrils (Barrachina et al, 2006; Gurney et al, 2018) and were found to be up‐regulated in brain and retinal tissues from old ADtg mice. In response to GA immunomodulation, we revealed a preferential down‐regulation of LAMP1 in the brain and LAMP2 in the retina.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a number of studies have proposed that basal levels of autophagy are important for the clearance of α-synuclein, thus limiting intracellular oligomerization and formation of aggregates ( Vogiatzi et al, 2008 ). Interestingly, studies on autophagic markers in the context of neurodegenerative disease namely, Dementia with Lewy bodies (DLB) has shown some alterations compared to controls ( Gurney, 2018 , Higashi et al, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the evidence from genetics, the involvement of lysosomal dysfunction in PD has been implicated from pathological and biochemical studies using postmortem disease samples. The reduction in the immunoreactivity of lysosomal markers, such as LAMP1 and cathepsin D, was detected in PD and Lewy body disease ( 22 , 23 ), and lysosomal breakdown, autophagosomal accumulation and the colocalization of autophagosomal markers with Lewy bodies were also detected in PD brains ( 24 ). Cathepsin D immunoreactivity has been shown to colocalize with α-synuclein pre-aggregates in nigral neurons in PD ( 25 ).…”
Section: Introductionmentioning
confidence: 99%